P-21 activated kinase 4 (PAK4) maintains stem cell-like phenotypes in pancreatic cancer cells through activation of STAT3 signaling. Issue 2 (28th January 2016) - Tyagi, Nikhil; Marimuthu, Saravanakumar; Bhardwaj, Arun; Deshmukh, Sachin K.; Srivastava, Sanjeev K.; Singh, Ajay P.; McClellan, Steven; Carter, James E.; Singh, Seema
Highlights: PAK4 is highly expressed in pancreatic cancer stem (CD24 + /CD44 + /ESA + ) cells. Silencing of PAK4 suppresses the markers and transcription factors associated with cancer stemness. PAK4 knockdown decreases pancreatic cancer stem cell phenotypes. STAT3 mediates PAK4-induced stemness of pancreatic cancer cells. Abstract: Pancreatic cancer (PC) remains a highly lethal malignancy due to its unusual chemoresistance and high aggressiveness. A subpopulation of pancreatic tumor cells, known as cancer stem cells (CSCs), is considered responsible not only for tumor-maintenance, but also for its widespread metastasis and therapeutic failure. Here we investigated the role of p-21 activated kinase 4 (PAK4) in driving PC stemness properties. Our data demonstrate that triple-positive (CD24 + /CD44 + /EpCAM + ) subpopulation of pancreatic CSCs exhibits greater level of PAK4 as compared to triple-negative (CD24 − /CD44 − /EpCAM − ) cells. Moreover, PAK4 silencing in PC cells leads to diminished fraction of CD24, CD44, and EpCAM positive cells. Furthermore, we show that PAK4-silenced PC cells exhibit decreased sphere-forming ability and increased chemosensitivity to gemcitabine toxicity. PAK4 expression is also associated with enhanced levels of stemness-associated transcription factors (Oct4/Nanog/Sox2 and KLF4). Furthermore, our data show decreased nuclear accumulation and transcriptional activity of STAT3 in PAK4-silenced PC cells and restitution of its activity leads to restoration of stem cell phenotypes. Together, our findings deliver first experimental evidence for the involvement of PAK4 in PC stemness and support its clinical utility as a novel therapeutic target in PC.